Modelagem de telhado verde: uma análise da eficiência no controle do escoamento pluvial em diferentes escalas - Lorenzini Neto, Francisco (2014)
Green roofs (GRs) have as one of its principal advantages the stormwater retention. To evaluate this quality at different spatial scales, and face to not observed events, hydrological modelling is required. In Brazil, studies related to the hydrological modelling of GRs are incipient. Thus, this research had as main objective the analysis of the efficiency of GRs in the stormwater runoff control at different spatial scales, simulating an urban watershed, where conventional roofs were replaced by GRs. To reach this objective were accomplished the following processes: monitoring of rainfall-runoff events of an experimental GR; calibration of the GR effective rainfall volume by the modified SCS-CN method; development of a rainfall-runoff hydrological model for the GR; design of a micro drainage networks system simulating the watershed without GRs and using design storms; simulation of the watershed with the implementation of GRs to evaluate the impact on the reduction of peak flows and volumes propagated into the drainage networks face to observed rainfalls. Calibrated average CN resulted in 83, staying within the expectations when compared to values found by other authors for GR with similar characteristics. In this calibration was also possible to notice the GR retained in average 45% of each rainfall event volume. In the development of the GR model, initially was calibrated the runoff propagation using models known in the hydrological field: kinematic wave (KW) and the synthetic unit hydrograph of the SCS (SCS-UH). None of these models produced satisfactory results, then was developed a propagation model based in the SCS-UH method, which was called synthetic unit hydrograph of modular GR (MGR-SUH), proposing changes in some of its parameters. MGR-SUH produced satisfactory results, with the Nash-Sutcliffe coefficient resulting in 0,86, which was substantially bigger than the values obtained using the KW and SCS-UH models (0,67). Related to the reduction of peak flow in the micro drainage networks, the implementation of GR in the plots allowed to reduce one commercial diameter in 33 and 52% of the drainage networks stretches, for systems designed to 5 and 10-year return period design rainfall, respectively. Reductions were possible at different scales, both in stretches located at beginning of network, with few blocks contributing, and stretches located at end of network, with several blocks contributing. Besides, it was evaluated the GR effect at the different analyzed scales, with bigger efficiency at small scale (in average, the volume and peak flow reductions at the plot scale were 48 and 57%, respectively), than at block(s) scale, where these reductions were 32 and 38%. Also was found that the biggest reductions happened in events of smallest rainfall volume. Thus, this research allowed to conclude that the effectiveness of the GR in the stormwater runoff control decreases as the scale used increases, and also as increases the volume and intensity of the rainfall.